EFFECTIVENESS OF TPS (THINKING, PAIRING AND SHARING) LEARNING MODEL ASSISTED BY QUIZIZZ TO TRAIN CRITICAL THINKING AND COLLABORATION SKILLS - Zuhrotun Najichah; Qonita Maulida; Nailil Inayah; Amiliyah Amiliyah (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2025)
The purpose of this study was to train critical thinking and collaboration skills through the TPS (Thinking, Pairing and Sharing) learning model assisted by Quizizz. The results of pre-research interviews with science subject teachers revealed that learning had not optimally practiced critical thinking skills and collaboration. This study used a quantitative experimental method with a quasi-experimental group design, where data were collected through tests and questionnaires distributed to 64 VIII grade students as research samples. The instruments used in this study were critical thinking skills test using Quizizz, collaboration skills questionnaire instrument, and TPS cooperative syntax implementation observation sheet instrument. The results of the study showed that the implementation of TPS (Thinking, Pairing and Sharing) cooperative learning model assisted by Quizizz had a significant increase in critical thinking skills and collaboration. The data that has been obtained shows 0.000 <0.05, which means that there is a significant change between the control and experimental classes. HOTS questions can hone critical thinking in the evaluation phase while the study group stage fosters students’ collaboration skills. The average value of critical thinking skills between control and experimental classes shows a difference of 83.6%, while the value of collaboration skills has a difference of 11.6%.